2020
DOI: 10.1016/j.jstrokecerebrovasdis.2020.105089
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Pandemic and Burden of Non-Communicable Diseases: An Ecological Study on Data of 185 Countries

Abstract: Background: The interaction between coronavirus disease 2019 (COVID-19) and noncommunicable diseases may increase the global burden of disease. We assessed the association of COVID-19 with ageing and non-communicable diseases. Methods: We extracted data regarding non-communicable disease, particularly cardiovascular disease, deaths, disability-adjusted life years (DALYs), and healthy life expectancy (HALE) from the Global Burden of Disease Study (GBD) 2017. We obtained data of confirmed COVID-19 cases, deaths,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
111
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 119 publications
(125 citation statements)
references
References 27 publications
7
111
0
7
Order By: Relevance
“…Widespread testing and contact tracing are crucial steps toward alleviating lockdowns and social distancing; however, they are not sufficient. It is crucial for policymakers to ensure adequate resources are also allocated toward populations at risk, including the elderly with vascular diseases and comorbidities [ 145 ].…”
Section: Resultsmentioning
confidence: 99%
“…Widespread testing and contact tracing are crucial steps toward alleviating lockdowns and social distancing; however, they are not sufficient. It is crucial for policymakers to ensure adequate resources are also allocated toward populations at risk, including the elderly with vascular diseases and comorbidities [ 145 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study, using the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) 2017 database [15], we observed a significant yet weak correlation between all non-communicable diseases, including ischemic stroke and ischemic heart diseases with COVID-19 confirmed cases and deaths. Furthermore, life expectancy and healthy life expectancy (HALE) had independent positive associations with COVID-19 caseload and mortality.…”
Section: Introductionmentioning
confidence: 86%
“…Several factors might have caused healthcare systems in high-income countries to be hit harder, besides the more pronounced aging of their populations, an added risk factor for COVID-19 mortality [ 17 ]. We know by now that the burden of nom-communicable disease, which is higher in high-income countries, is strongly correlated with the severity and mortality of COVID-19 [ 18 , 19 ]. COVID-19 severity and mortality are also strongly associated with older age.…”
Section: Health Care Services Have and Are Still Struggling To Resilmentioning
confidence: 99%